2013
DOI: 10.1002/2013jd019818
|View full text |Cite
|
Sign up to set email alerts
|

A global view of the atmospheric lunar semidiurnal tide

Abstract: Atmospheric lunar semidiurnal tides are studied using 10 years of temperature data collected by the Thermosphere Ionosphere Mesosphere Energetics and Dynamics/Sounding of the Atmosphere Using Broadband Emission Radiometry satellite. The amplitudes and phases in the temperature field are calculated by performing least mean square fit in a data set of about 60 day interval (combining ascending and descending data together). The mean tidal structures are studied for the height range from 20 to 120 km, between ±50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 33 publications
3
42
3
Order By: Relevance
“…It is well‐known that during northern winter months, there are significant longitudinal differences in the stratosphere and MLT dynamics [e.g., Hoffmann et al , ]. Similarly, Paulino et al [] has reported longitudinal variations of M 2 amplitudes within ±50° latitudes using MLT temperatures from SABER. These observations point to the importance of the nonmigrating components of the lunar tides.…”
Section: Discussionmentioning
confidence: 98%
“…It is well‐known that during northern winter months, there are significant longitudinal differences in the stratosphere and MLT dynamics [e.g., Hoffmann et al , ]. Similarly, Paulino et al [] has reported longitudinal variations of M 2 amplitudes within ±50° latitudes using MLT temperatures from SABER. These observations point to the importance of the nonmigrating components of the lunar tides.…”
Section: Discussionmentioning
confidence: 98%
“…Most previous studies on the atmospheric lunar tide focused on the migrating (i.e., Moon‐synchronous) component (Forbes et al, ; Lieberman et al, ; Zhang & Forbes, ). An exception is the work by Paulino et al (), which took into account possible contributions by nonmigrating (i.e., not Moon‐synchronous) tides. They performed a spectrum analysis of the M 2 tide in the temperature data taken from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) instrument on board the Thermosphere Ionosphere Mesosphere Energetics Dynamics (TIMED) satellite.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the lunar tidal amplitudes are found to be weaker over Pacific sector. Both Paulino et al [] and Pedatella and Forbes [] observed longitudinal variations in the lunar tide in temperature and GPS‐TEC, respectively, and attributed them to the presence of nonmigrating tides. The ocean and solid earth tidal forcing can generate the nonmigrating tides, which may propagate vertically and generate significant longitudinal variability [ Vial and Forbes , ].…”
Section: Discussionmentioning
confidence: 99%